The Combination of Imaginative Teaching Methods and Multimedia Learning in Early Childhood Education during COVID Pandemic: Social-Emotional and Language Development - Yafie, Evania; Olufunke, Olusola-Fadumiye Titilope; Ali, Manal; Robbaniyah, Inayatur; Maulidia, Lisa Nur; Setyaningsih, Diana (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This study aimed to identify whether there is an increase in social-emotional and language aspects’ enhancement through the combination of imaginative teaching methods and multimedia learning that the teacher carried out.Design/methods/approach – This is a quantitative study that applies the pre-experimental design method. The model applied through this research was in the form of a pretest-posttest group which was carried out by comparing the emotional abilities of children before and after being given treatment in the form of a combination of imaginative processing methods and multimedia learning. The sampling technique used purposive sampling where the research subjects were in their early childhood, aged 5-6 years.Findings – Imaginative teaching approaches and multimedia-based learning impact the development and improvement of children's socio-emotional and language development. This can be seen from the comparison between the post-test scores that are more significant than the pre-test scores, namely, and the significance value on all dimensions is 0.000 <0.05.Research implications/limitations – In this study, the use of pretest and posttest methods in experimental design helps to clarify differences in the provision of imaginative processing methods and multimedia learning. The obstacles faced by the majority relate to the internet connection in communicating with teachers.Practical implications – The combination of imaginative learning methods and multimedia learning improves language social-emotional aspects effectively. The results of this study contribute to understanding for teachers and school institutions to better utilize information and communication technology in optimizing child development. Paper type Research paper